NEW MONUMENTS OF THE КUSHAN PERIOD OF THE NORTHERN BACTRIA (Scientific journal of the Fergana State University, 2023)
The given article elucidates the initial information on archeological investigations of the new relics, related to the cattlebreeding cultures of the northern Bactria